ATRT-14. Malignant rhabdoid tumors of cranial nerves – ATRT or extracranial rhabdoid tumor?. (3rd June 2022) - Gruhle, Miriam; Nemes, Karolina; Steinbügl, Mona; Johann, Pascal D; von Luettichau, Irene; Steinborn, Marc; Tippelt, Stephan; Fleischhack, Gudrun; Lehrnbecher, Thomas; Bens, Susanne; Siebert, Reiner; Hasselblatt, Martin; et al.
Abstract: INTRODUCTION: Malignant rhabdoid tumors (MRT) are highly aggressive neoplasias mostly affecting young children. They are classified as rhabdoid tumors of the central nervous system (ATRT, atypical teratoid rhabdoid tumor), rhabdoid tumors of the kidney (RTK) or extracranial rhabdoid tumors arising from any soft tissue outside the central nervous system (eMRT, extracranial extrarenal MRT). We report a series of four MRTs with cranial nerve involvement. METHODS: Patients were identified from a cohort of 132 patients with MRT (2017 – 2021), as part of the European Rhabdoid Registry (EU-RHAB). Diagnosis of MRT was confirmed immunohistochemically with loss of INI1 expression. Details regarding symptoms at first presentation, diagnostic staging, genetic findings, therapy and the course of disease are reported. REPORT OF CASES/RESULTS: The series contains two MRT affecting the trigeminal nerve and two cases with third cranial nerve involvement. They were two female and two male patients with a median age of 4.7 years (1-159 months) at diagnosis. Location of the main tumor mass differed between being located intra- and extracerebrally. Metastases at diagnosis occurred in one patient, a germ-line mutation in SMARCB1 was present in two patients. Two patients received therapy according to EU-RHAB recommendations with an incomplete resection, conventional chemotherapy enhanced by intraventricular methotrexate and radiotherapy. Both patients are currently alive with no signs of progression, one of them bearing a germ-line mutation. Two patients received palliative treatment after surgery due to rapid progression. Median overall survival was 17.3 (1.4-53.1) months. CONCLUSION: MRT of the cranial nerves affect the peripheral nervous system in close proximity to the brain, thus forming a unique sub-entity between ATRT and eMRT. The selected cases provide insight into the particular challenge regarding clear classification, diagnostics and therapy.